Persepsi Masyarakat Terhadap Revitalisasi Pasar Tradisional di Pasar Rakyat Banjar, Desa Banjar, Kabupaten Buleleng - Kadek Irma widya Darini; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aimed at determining public perception of traditional market revitalization in Banjar people's market. The type of research was a descriptive study with a quantitative approach to describe the public perception of traditional market revitalization in Banjar people's market. The population in this study are visitors at the Banjar people market with a sample of 405 respondents who were searched using the sampling incidental. Data were collected by questionnaires and analyzed using descriptive analysis. Based on the result of the study, public perception of the expectation dimension obtained a score of 23.798 included in the appropriate category, the need dimension obtained a score of 7.090 included in the strongly agree category, the experience dimension obtained a score of 9.543 included in the good category.